Potential Test Of Ethanol Extract From Onion (Allium Cepa L) Leaves As A Repellent To Aedes Aegypti - Adnani, Basyar; Rahmah, Zainabur; Fitrianingsih, Avin Ainur; Setiawan, Abdul Malik (Journal of Islamic Medicine, 2020)
Background : The most dangerous vector of mosquito-borne disease, namely Dengue Haemorrhagic Fever (DHF), is Aedes aegypti. One of the most commonly used prevention methods is using repellent.Objective: This study aims to know red onion (Allium cepa L) leaves ability as a repellent against mosquitoes bites, primarily Aedes aegypti. Onion leaves are known to have flavonoids and essential oil content that believed to have health benefits such as anti-inflammatory, insecticide, antifungal, and repellency effects.Method: This study design was a post test only control group of true experiment, with Â± 300 mosquitoes in five treatment groups. The study design was a true experimental post-test only control group using Â± 300 mosquitoes divided into five treatment groups. Positive control, negative control, and three groups with each extract containing 5%, 10%, and 20% content. The data taken is the number of mosquitoes alighted on attractants available, for five consecutive days. The analytical test used is the KruskalWalls and Spearman test with Î± coefficient 0.05.Results: the number of mosquitoes perching on each of the extract treatment plates decreased with increasing extract concentration. In the treatment control group, the negative control had the highest number of mosquitoes perching, while the positive control had the least number of perching mosquitoes. All concentrations of ethanol extract, either 10%, 15%, or 10%, all have the effect of repellent against Aedes aegypti.Conclusion : 20% of ethanol extract has the most repellency effect on Aedes aegypti mosquitoes.